OBESITY AS AN INDICATOR OF HYPERTENSION AT THE ELDERLY HEALTH CARE POSYANDU IN SUSUKAN REJO VILLAGE PASURUAN - Lia Dwi Adinda Putri; Ratna Roesardhyati; Apriyani Puji Hastuti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Among older adults, hypertension represents a significant public health concern that is often linked to excess body weight. Obesity, a modifiable risk factor, is known to elevate blood pressure and contribute to related complications in later years. This makes it a critical measure for assessment within elderly communities. Methods: Employing a quantitative, descriptive correlational design with a cross-sectional method, this research was carried out at an Elderly Integrated Health Post in Susukan Rejo Village, Pasuruan. A total of 70 pre-elderly and elderly participants were included via total sampling. Obesity was evaluated using body mass index and waist circumference, and blood pressure was measured following standard protocols. Data were examined through univariate analysis and bivariate analysis using the Chi-square test to explore the relationship between obesity and hypertension. Results: The study revealed a high prevalence of obesity according to both body mass index and waist circumference. A majority of respondents were diagnosed with hypertension, most commonly at stage 1. Bivariate analysis indicated a statistically significant association between obesity and hypertension, with greater obesity linked to more advanced stages of hypertension. Conclusions: Obesity was found to be a strong predictor of hypertension in the studied elderly population. These findings highlight that weight management through lifestyle changes, consistent health monitoring, and community-led programs could be vital for lowering hypertension risk and enhancing health outcomes among older adults.